PENGARUH METODE DEMONSTRASI TERHADAP KEMAMPUAN MENGENAL BENTUK GEOMETRI ANAK USIA 4–5 TAHUN DI KB PUCUK REBUNG DAUN BERJALIN RUMBAI PEKANBARU - Renny Syafputri; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims 1) To determine the geometric shape recognition before the demonstration method in children aged 4-5 years KB Pucuk Rebung Daun Berjalin Rumbai Pekanbaru. 2) To determine the geometric shape recognition after the demonstration method in children aged 4-5 years in KB Pucuk Rebung Daun Berjalin Rumbai Pekanbaru. 3) To know how big demonstration against the introduction of the method of geometric shapes in children aged 4-5 years in KB Pucuk Rebung Daun Berjalin Rumbai Pekanbaru. This type of research used in this research is the experimental approach of a study that sought influence of certain variables on other variables in strictly controlled conditions. The study sample that children KB Pucuk Rebung Daun Berjalin Rumbai Pekanbaru with the number of children 15, 8 boys and 7 girls. Collecting data using observation and documentation. Collecting data using observation and documentation. Based on the survey results revealed that 1) the geometric shape recognition ability of children aged 4-5 years in KB Pucuk Rebung Daun Berjalin Rumbai Pekanbaru before treatment is given in the form of demonstration methods is low. 2) The ability of recognition of geometric shapes children aged 4-5 years in KB Pucuk Rebung Daun Berjalin Rumbai Pekanbaru after treatment is given in the form of demonstration methods has increased and is high. 3) demonstration method has a significant impact on the ability of recognition of geometric shapes children aged 4-5 years in KB Pucuk Rebung Daun Berjalin Rumbai Pekanbaru. It can be seen that there are differences related to increase the recognition of geometric shapes children before and after treatment. Demonstration method has the effect of 42.22% of the geometric shape recognition ability of children aged 4-5 years in KB Pucuk Rebung Daun Berjalin Rumbai Pekanbaru.Keywords: Methods Demonstration, Shape Geometry